2017
DOI: 10.1515/amsc-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Method of Roof Fall Susceptibility Assessment based on Fuzzy Approach

Abstract: Retreat mining is always accompanied by a great amount of accidents and most of them are due to roof fall. Therefore, development of methodologies to evaluate the roof fall susceptibility (RFS) seems essential. Ghasemi et al. (2012) proposed a systematic methodology to assess the roof fall risk during retreat mining based on risk assessment classic approach. The main defect of this method is ignorance of subjective uncertainties due to linguistic input value of some factors, low resolution, fixed weighting, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The loss of longwall stability, which reveals itself in the form of minor or major roof falls (Fig. 1), generally exists in all underground mines and has been confirmed in the form of statistical data from hard coal mines located in Poland, as well as in the USA, India, Iran, Turkey and China (Biliński, 1968;Ghasemi et al, 2017;Gu et al, 2018;Iannacchione et al, 2007;Mark et al, 2011;Martyka et al, 2013;Palei et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The loss of longwall stability, which reveals itself in the form of minor or major roof falls (Fig. 1), generally exists in all underground mines and has been confirmed in the form of statistical data from hard coal mines located in Poland, as well as in the USA, India, Iran, Turkey and China (Biliński, 1968;Ghasemi et al, 2017;Gu et al, 2018;Iannacchione et al, 2007;Mark et al, 2011;Martyka et al, 2013;Palei et al, 2008).…”
Section: Introductionmentioning
confidence: 82%
“…The proposed classification of roof fall hazard during retreat mining in the form of the level of roof fall risk (R rf ), when R rf < 28 the roof fall risk category is low and at an acceptable level, but when R rf > 70 the roof fall risk is unacceptable due to all parameters being in their most risky condition. Another methodology is presented in (Ghasemi et al, 2017) to assess the roof fall risk (RFS) using the fuzzy approach in order to identify the susceptibility of roof fall occurrence. In Table 2 was shown the making decision model components formed by (Ghasemi et al, 2017).…”
Section: Value Of Index 'G'mentioning
confidence: 99%
See 1 more Smart Citation
“…Roof fall accidents are predicted using binary logistic regression model [4]. Roof fall risk is identified using risk assessment classical methodology [5] with fuzzy based approach. It projects that the roof fall is due to various features like low resolution, fixed weighting, sharp class boundaries of the building.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…By using AHP, Yang et al suggested a fuzzy evaluation model for mine water and sand inrush caused by underground mining [37]. By using fuzzy AHP to prioritize risk factors, Ghasemi et al presented a methodology to evaluate the roof fall susceptibility during retreat mining [38]. Wang et al suggested a fuzzy fault tree analysis method to evaluate the risk of coal dust explosions [39].…”
Section: Introductionmentioning
confidence: 99%